Anthropogenic Influences on the Chemical and Mineral Composition in Pond Sediment by X-Ray Absorption Spectroscopy and X-Ray Powder Diffraction - Jalal Sawas; Derek Blanco; Mary Kroll; Aleida Perez; Juergen Thieme; Eric Dooryhee; Sarah Nicholas; Paul Northrup; Dana Schaefer (Quantum Beam Science)
Manmade detention ponds have historically been impacted by anthropogenic activities such as rainwater runoff, car emissions, and drainage from infrastructures, which can lead to complications for pond ecosystems. Sediment samples collected from the northern, southern, western, and eastern regions of a small pond on a suburban high school campus on Long Island, NY, were analyzed for potential chemical changes resulting from an inundation of water by a broken water main. Incorporating synchrotron X-ray techniques, sediment was analyzed using Submicron Resolution Spectroscopy, Tender Energy X-ray Spectroscopy, and X-ray Powder Diffraction to examine heavy metals, light elements, and minerals. Results include a Zn:Cu ratio increase from 4:1 to 10:1 in the eastern zone and a higher heavy metal presence in the western zone for all elements examined, with greater distribution throughout the pond post-inundation. Lighter elements appear to remain relatively unchanged. The appearance of diopside in the eastern zone post-inundation samples suggests contamination from the water main break, while the presence of carbonate minerals in the western zone is consistent with erosion of asphalt material from the adjacent parking lot.